2017
DOI: 10.1186/s12916-016-0769-1
|View full text |Cite
|
Sign up to set email alerts
|

About the complexity of adult onset Still’s disease… and advances still required for its management

Abstract: Adult onset Still’s disease (AOSD) is a rare inflammatory disorder that remains poorly understood. Its pathophysiology is yet to be completely elucidated, but is known to consist mainly on a cytokine cascade, responsible for the systemic manifestations. AOSD diagnosis is usually difficult and delayed, with physicians having to rule out several other conditions, including cancer or infectious diseases. Prognosis is heterogeneous and difficult to establish, ranging from benign outcome to chronic destructive poly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
12
0
2

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 17 publications
(31 reference statements)
1
12
0
2
Order By: Relevance
“…Further, it has been shown that MAS occurrence may be misdiagnosed in patients treated with immunosuppressive agents used to control AOSD clinical features 13,14,28 . Of note, serum ferritin levels, systemic score values, prevalence of lymphadenopathy, and liver involvement were significantly higher at the time of diagnosis in those patients with AOSD who had MAS, identifying a subset of AOSD patients with a more aggressive disease, as previously shown 38,39 . We also observed that the patients experiencing MAS during the followup showed, at the time of diagnosis, increased systemic score values and higher prevalence of abdominal pain when compared with AOSD patients not developing this complication.…”
Section: Discussionsupporting
confidence: 53%
“…Further, it has been shown that MAS occurrence may be misdiagnosed in patients treated with immunosuppressive agents used to control AOSD clinical features 13,14,28 . Of note, serum ferritin levels, systemic score values, prevalence of lymphadenopathy, and liver involvement were significantly higher at the time of diagnosis in those patients with AOSD who had MAS, identifying a subset of AOSD patients with a more aggressive disease, as previously shown 38,39 . We also observed that the patients experiencing MAS during the followup showed, at the time of diagnosis, increased systemic score values and higher prevalence of abdominal pain when compared with AOSD patients not developing this complication.…”
Section: Discussionsupporting
confidence: 53%
“…To date, determining predictive factors of outcome and to drawing guidelines for patient management remains difficult 14, 15 . Previous studies, including ours, have demonstrated elevated levels of proinflammatory cytokines including interleukin (IL)-1β, IL-6, IL-18, tumor necrosis factor (TNF)-α, and type 1 T helper (Th1)- or Th17-derived cytokines in AOSD patients 1621 .…”
Section: Introductionmentioning
confidence: 99%
“…MAS is a life-threatening complication of rheumatic disorders, including sJIA, adult-onset Still's disease (AOSD) and lupus. [1][2][3][4] Timely diagnosis and appropriate treatment of MAS are particularly important to improve the prognosis of MAS patients. At present, hemophagocytic lymphohistiocytosis (HLH)-2004 and HLH-2009 criteria are widely used to identify MAS associated with AOSD.…”
mentioning
confidence: 99%